Implementation of the PPG Leadership Project for Prospective Teachers at Pasundan University through the Green Bites Program: Educating about Healthy Menus Based on Local Vegetables - Hafit Nuroswandi; Jaka Rukmana; Dahlia Fisher; Siti Wahyuni; Alya Karima; Salma Aulia Rahmatillah; Alsya Yulkha Putri; Bagas Hamdanirahman; Ajeng Zulfa Salsabila; Devi Tri Herlanda; Titis Dwi Nurhannisa (Jurnal Pengabdian Sains dan Humaniora, 2025)
Low vegetable consumption and the lack of skills in processing local food into healthy meals are ongoing nutritional issues in various regions of Indonesia, including in Cibangkong Village, Bandung City. This activity aims to increase consumption and skills in processing local food into healthy meals by PKK mothers through training in processing local vegetables into Pakcoy Nori and vegetable nuggets. The activity methods include preparation, implementation, and analysis of results. The activity began with observation, training involving PPG Candidate Teacher students and the Faculty of Food Technology, Pasundan University as mentors, and practical training in making Pakcoy Nori and vegetable nuggets. The results of the activity showed improved skills of participants in processing and packaging healthy food products, increased nutritional awareness, and an interest in turning these products into business opportunities. This project concludes that training in appropriate local vegetable processing can be a strategic solution to address nutrition issues, build family food independence, and encourage a sustainable local economy.